Effect of Home Enteral Nutrition on Diabetes and Its Management. (13th July 2018) - Vallumsetla, Nishanth; Epp, Lisa; Hurt, Ryan T.; Mundi, Manpreet S.
Abstract: Background: Diabetes mellitus (DM) is estimated to affect 9% of Americans and is associated with significant morbidity, mortality, and increased healthcare costs. Methods: A retrospective review of a home enteral nutrition (HEN) database of patients seen between March 1, 2004, and April 31, 2014, at our institution was conducted to identify HEN patients who had a diagnosis of DM or were diagnosed within the acute period (4 months) of starting HEN therapy. Results: 174 (3.7%) of 4682 patients in the HEN program had DM. HEN was provided through a gastrostomy tube in 82 patients and through a jejunostomy tube in 92 patients. At 3 months, data were available for 42 gastrostomy patients; 44% had a change in DM management, with 60% undergoing a change to insulin. Similarly, 34 patients with jejunostomy had data available, with 41% undergoing change in medication and 93% being changed to insulin therapy. For patients with available glycated hemogloblin values, at 3 months the gastrostomy patients noted a decrease of 0.5% (7.3% ± 1.1% to 6.8% ± 0.7%, not significant) and the jejunostomy patients noted a decrease of 0.4% (6.9% ± 0.9% to 6.5% ± 1.1%, P = .06). Conclusions : Overall, our results suggest that closer follow‐up and laboratory assessment are necessary for management of HEN patients with DM. In those with data available, glycemic control can be maintained in patients receiving HEN with appropriate adjustment of DM management and focus on ensuring that patients are not overfed.